Second-generation ethanol process for integral use of hemicellulosic and cellulosic hydrolysates from diluted sulfuric acid pretreatment of sugarcane bagasse - Dionísio, S. R.; Santoro, D. C.J.; Bonan, C. I.D.G.; Soares, L. B.; Biazi, L. E.; Rabelo, S. C. [UNESP]; Ienczak, J. L. (Elsevier, 2021)
In this work, a strategy to promote ethanol fermentation through the complete utilization of fermentable sugars released from sugarcane bagasse was proposed. Initially, the sugarcane bagasse was subjected to a diluted sulfuric acid pretreatment, leading to 89.5% of hemicellulose solubilization, in which 82% was recovered as monomeric sugars (xylose and arabinose) in the liquid stream. The cellulignin obtained was subjected to enzymatic hydrolysis, resulting in 51.2 and 95.08% of cellulose and hemicellulose yields, respectively. The C5-rich hemicellulosic hydrolysate was fermented to ethanol by the pentose-fermenting yeast Spathaspora passalidarum NRRL Y-27907, achieving an ethanol yield of 86.11%. The C6-rich enzymatic hydrolysate, on the other hand, was fermented by Saccharomyces cerevisiae CAT-1 through the application of a cell-recycle batch fermentation system. This strategy improved the overall fermentation performance throughout the cycles, with a substantial increase in the ethanol productivity of 361% from the first to the last batch. Based on a mass balance with input of 1000 kg of sugarcane bagasse and taking into account a complete pentose and hexose fermentation, 191.96 kg of ethanol could be produced from this integrated platform, which corresponded to 243.3 L of ethanol.
Keywords: C5+C6 separated fermentation; Cell recycle; Diluted acid pretreatment; Sugarcane bagasse